Efficacy of Technical Analysis to Assess Fair Value Gap: Evidence from Nepalese Commercial Bank (Sudurpaschim Spectrum, 2024)
This paper examines the efficacy of the selected technical indicators to identify fair value gaps meant for stock investment and trade optimization based on the technical signals of the Banking sector stocks listed in the Nepal Stock Exchange (NEPSE). The analysis focuses on Simple Moving Averages (SMA), Moving Average Convergence Divergence (MACD), Bollinger Bands (BB), Relative Strength Index (RSI), and Fibonacci Retracement as key indicators. Findings reveal that the selected technical indicators provide reliable ground to explore fair value gap and better market entry and exit signals for optimizing investment, aligning with standard technical analysis principles. Therefore, the study underscores the significance of using multiple indicators for robust decision-making for stock market investment, particularly in emerging markets like Nepal, where market inefficiencies and volatility is common phenomena. Moreover, the results have practical implications for all market participants including traders, investors, and analysts. Future research should may choose other indicators to support this strategy to develop more comprehensive trading models.